2018
DOI: 10.30870/jpsd.v4i2.3852
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Model Collaborative Problem Solving (Cps) Dalam Meningkatkan Kemampuan Representasi Matematis Mahasiswa Calon Guru Sekolah Dasar

Abstract: Representasi matematis penting bagi mahasiswa untuk menyampaikan ide-ide kreatif terhadap permasalahan statistik. Pentingnya representasi matematis, maka tujuan penelitian ini adalah menganalisis perbedaan peningkatan representasi matematis mahasiswa calon guru sekolah dasar yang difasilitasi dengan menggunakan model collaborative problem solving. Metode yang digunakan adalah Quasi Eksperiment dengan desain Non-equivalent Pretest-Posttest Control Group. Sampel penelitian sebanyak 70 mahasiswa calon guru sekola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…To analyze the feasibility of the CPS learning model, the feasibility rating model was used. Table 1 presents the feasibility rating of the CPS learning model that refers to The New Teacher Project (Takaria, 2015;Takaria & Talakua, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the feasibility of the CPS learning model, the feasibility rating model was used. Table 1 presents the feasibility rating of the CPS learning model that refers to The New Teacher Project (Takaria, 2015;Takaria & Talakua, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical representation in statistical literacy learning for students is important, because students can convey mathematical ideas in various forms (tables, graphs, symbols, meaning of words, and mathematical equations) from something seen/observed through statistical information obtained on various media and the student's ability to give meaning to this information (Takaria & Talakua, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Model-model pembelajaran yang dapat digunakan untuk meningkatkan kemampuan representasi matematis antara lain: problem-based learning (Noer & Gunowibowo, 2018;Susilawati, Chandra, & Abadyo, 2019), collaborative problem solving (Takaria & Talakua, 2018) dan think pair share (TPS) (Arnidha, 2016). Model TPS ini juga terbukti mampu meningkatkan kemapuan komunikasi matematis (Abdi & Hasanuddin, 2018;Wahyuni, Hendryawan, Nasrullah, & Wachyar, 2018), kemampuan pemecahan masalah (Dwita, Bharata, & Noer, 2018), dan hasil belajar matematika (Ardinata, Siswantoro, & Suwarjo, 2018).…”
Section: Pendahuluanunclassified
“…Her dissertation implies that contextual learning can be applied to students of Madrasah Aliyah to improve their statistical reasoning skills and self-efficacy (Ulpah, 2013). Takara concluded that there was an increase in statistical literacy skills and mathematical and self-concept representation of prospective elementary school teachers taught through the Collaborative Problem Solving model (Takaria, 2018). (Lanani, 2015) shows that the achievement of statistical reasoning ability of students who obtain ICT-assisted project-based learning is higher than students who obtain conventional learning, both at each class level and overall.…”
Section: Introductionmentioning
confidence: 99%